A self-startup DC-DC boost converter for thermal energy harvesting in a 0.35 μm CMOS process - Eun Jeong Yun; Chong Gun Yu (Institute of Advanced Engineering and Science, 2022)
In this paper a self-startup DC-DC boost converter for thermal energy harvesting applications is presented. A startup circuit boosts an internal supply voltage using a low voltage generated from a thermoelectric generator to operate the internal circuitry of the converter. To reduce power dissipation, the startup circuit is disabled after the startup operation is finished. A boosted output voltage is obtained by alternating an auxiliary converter for the internal supply voltage and a main converter for the output voltage. The converter has been implemented in a 0.35 μm complementary metal–oxide–semiconductor (CMOS) process. Measurement results shows that the designed converter is capable of generating an output voltage close to 3V from an input voltage of 200 mV, and can provide a maximum output power of 278 μW with an end-to-end power efficiency of 46.5%. It occupies an active area of 0.36 mm2.